Od Ewangelii o Jezusie pełnym mocy do Ewangelii krzyża - Witczyk, Henryk (Verbum Vitae, 2002)
Four genres of the original Gospel kerygma present images of Christ in the New Testament, each portraying the face of Jesus in their historical-literary context. John the Baptist teaches about Gods judgement in the presence of the Saviour from Nazareth, who will baptise in the Holy Spirit and fire. Jesus preaches the Good News of conversion and forgiveness, and is the one who has come to bring Gods goodness and love, inviting men to a new life and salvation. Peter proclaims the Gospel at Pentecost as the full revelation of Gods power shown by the presence of Jesus risen from the dead. Paul is rejected by the Greek intelligentsia in Athens for teaching these same truths of Jesus death and resurrection. His Gospel message becomes the proclamation of Jesus cross, the loving death of Christ, which is the beginning of the Good News of salvation for the world. For Paul, Christs resurrection stems from his death on the cross, a loving sacrifice. All Christians must meditate on and teach of Christs cross in order to build the Church today just as the first apostles did when bringing the Good News of salvation with its full power to convert the hearts of people.